MENINGKATKAN KEMAMPUAN MENULIS KARANGAN NARASI MELALUI MEDIA VIDEO ANIMASI PADA SISWA KELAS III SD NEGERI - Usman, Fadilah S; Husain, Rusmin; Pulukadang, Wiwy Triyanty; Monoarfa, Fidyawati; Husain, Rustam I. (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study is a classroom action research (CAR) aimed at demonstrating the improvement of students’ narrative writing skills through the use of animated video media. The research problem addressed is that the use of animated video media can enhance the narrative writing ability of third-grade students at SDN 04 Dulupi, Boalemo Regency. The research subjects were 15 third-grade students who served as the main participants. Data were collected through observation, interviews, tests, and documentation, and were analyzed to assess the development of students’ writing skills in each cycle. Initial observations revealed that only 3 students (20%) were able to write narrative texts, while 12 students (80%) were not yet able to do so. In the first meeting of the first cycle, the number of capable students increased to 6 (40%), and in the second meeting, this number rose to 10 (60%). Improvements implemented in the second cycle resulted in a significant increase, with 13 students (87%) achieving the expected writing ability, and only 2 students (13%) remaining below the target. These findings indicate that the application of animated video media is effective in enhancing the narrative writing skills of third-grade students at SDN 04 Dulupi, Boalemo Regency. ABSTRAKPenelitian ini termasuk dalam jenis penelitian tindakan kelas (PTK) yang bertujuan untuk membuktikan peningkatan kemampuan menulis karangan narasi siswa melalui penggunaan media video animasi. Rumusan masalah yang diangkat adalah penggunaan media video animasi dapat meningkatkan kemampuan menulis karangan narasi pada siswa kelas III SDN 04 Dulupi Kabupaten Boalemo. Subjek penelitian adalah 15 siswa kelas III yang menjadi partisipan utama. Data dikumpulkan melalui observasi, wawancara, tes, dan dokumentasi, kemudian dianalisis untuk melihat perkembangan keterampilan menulis siswa pada setiap siklus. Hasil observasi awal menunjukkan bahwa hanya 3 siswa (20%) yang mampu menulis karangan narasi, sedangkan 12 siswa (80%) belum mampu. Pada siklus I pertemuan pertama, jumlah siswa yang mampu meningkat menjadi 6 siswa (40%), dan pada pertemuan kedua bertambah menjadi 10 siswa (60%). Perbaikan yang dilakukan pada siklus II menghasilkan peningkatan signifikan, yaitu 13 siswa (87%) sudah mencapai kemampuan yang diharapkan, sedangkan hanya 2 siswa (13%) yang belum. Temuan ini membuktikan bahwa penerapan media video animasi efektif dalam meningkatkan keterampilan menulis karangan narasi siswa kelas III SDN 04 Dulupi Kabupaten Boalemo.